Evaluation of cephalometric changes in patients with class III malocclusion in mixed dentition period following face mask therapy and slow maxillary expansion - Ahmad Akhondi MS.; Khorshidian A.; Chalipa J. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: Among different treatments of patients with Class III malocclusion , orthopedic protraction of maxilla has been known as an effective method in mixed dentition period. The aim of this study was to evaluate the cephalometric changes of Cl III patients in mixed dentition period following face mask therapy and slow maxillary expansion. "nMaterials and Methods: This was a before-after study which was conducted on 10 children in mixed dentition period, who had class III malocclusion and maxillary deficiency according to the Stiener and Mc Namara's analysis. The patients were all treated by protraction face mask and slow maxillary expansion. The cephalometric changes of maxilla , mandible and dental relations during the treatment were analyzed by Paired sample T Test. P<0.05 was considered as the level of significant. "nResults: The overjet increasement was 1.7mm. Co. ANS distance improvement was 5.6mm, Ptm.ANS distance increasing was 3mm, and ultimately improvement of Gf.s distance was 1.5mm which were all statistically significant (p<0.05). "nConclusion: Based on the results of this study, face mask therapy with slow maxillary expansion is able to improve the horizotal position of maxilla, in patients with Cl III malocclusion , in mixed dentition period.